2020
DOI: 10.1155/2020/1210485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Web Openings on Flexural Behaviour of Underground Metro Station RC Beams under Static and Cyclic Loading

Abstract: This paper investigates the influence of multiple transverse web openings on the flexural behaviour of underground metro station reinforced concrete (RC) beams. This problem is outlined with an actual underground engineering project, in which the web opening used in the RC beams violates the current specifications. A total of five beams with different numbers of web openings are fabricated and tested under static and cyclic loading conditions, thereby simulating actual operations in unfavourable conditions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Experimental studies on RC beam-column joints with openings on the beam web have demonstrated the effectiveness of various reinforcement strategies in improving their cyclic performance. For example, researchers have found that the provision of supplementary transverse reinforcement around the openings can enhance the confinement of the concrete, thereby increasing the joint's load-carrying capacity and energy dissipation under cyclic loading [38]. Moreover, extending longitudinal reinforcement through the openings and providing adequate anchorage can ensure better force transfer and maintain the structural integrity of the joint.…”
Section: Beam-column Joints With Opening Under Cyclic Loadingmentioning
confidence: 99%
“…Experimental studies on RC beam-column joints with openings on the beam web have demonstrated the effectiveness of various reinforcement strategies in improving their cyclic performance. For example, researchers have found that the provision of supplementary transverse reinforcement around the openings can enhance the confinement of the concrete, thereby increasing the joint's load-carrying capacity and energy dissipation under cyclic loading [38]. Moreover, extending longitudinal reinforcement through the openings and providing adequate anchorage can ensure better force transfer and maintain the structural integrity of the joint.…”
Section: Beam-column Joints With Opening Under Cyclic Loadingmentioning
confidence: 99%
“…It has been shown that the influence of the openings on the load-bearing and seismic performance of the RC beams can be reduced by adding extra reinforcements around the openings. Openings' configuration was investigated in and an increase in ultimate load capacity when circular openings were used was reported [11]. These codes typically cover aspects such as load combinations, material properties, structural analysis, reinforcement detailing, and construction practices relevant to RC beams.…”
Section: Introductionmentioning
confidence: 99%